Does a Brief Motivational Intervention Reduce Frequency of Pregaming in Mandated Students?. (2nd July 2016) - Borsari, Brian; Merrill, Jennifer E.; Yurasek, Ali; Miller, Mary Beth; Carey, Kate B.
ABSTRACT: Background : Pregaming, also known as frontloading or predrinking, is a common but risky drinking behavior among college students. However, little is known about the way in which a brief motivational intervention (BMI) addressing general alcohol use and consequences may impact pregaming frequency. Objectives : This study examined whether mandated students reduced frequency of pregaming following a BMI when pregaming was spontaneously discussed and whether gender moderated these effects. Methods : Participants ( n = 269, 32% female) were mandated college students who had received a campus-based alcohol citation and continued to exhibit risky alcohol use six weeks after receiving a brief advice session. Participants were randomized to a brief motivational intervention (BMI, n = 145) or assessment only (AO, n = 124) and completed follow-up assessments at 3, 6, and 9 months postintervention. Hierarchical Linear Modeling (HLM) was used to examine both between-person (Level 2) effects (i.e., condition) and within-person (Level 1) effects (i.e., time) on pregaming frequency. Analyses examining discussions of pregaming within the BMI were conducted using a subsample of the BMI sessions which had been transcribed ( n = 121). Results : Participants in the BMI group did not significantly reduce the frequency of pregaming compared to those in the AO group, even when pregaming was explicitly discussed during the BMI. Moreover, the BMI was equally ineffective at reducing pregaming frequency for both males and females. Conclusion/Importance : Pregaming frequency appears to be resistant to conventional intervention efforts, but recent research suggests several innovative strategies for addressing pregaming in the college student population.